Subinhibitory Antibiotic Concentrations Enhance Biofilm Formation of Clinical Enterococcus faecalis Isolates - Bernardi, Sara (Antibiotics (Basel), 2021)
Enterococcus faecalis is a microorganism that can be found in the oral cavity, especially in secondary endodontic infections, with a prevalence ranging from 24–70%. The increase in the ability to form biofilms in the presence of subinhibitory antibiotic concentrations is a phenomenon that is observed for a wide variety of bacterial pathogens and is associated with increased resistance. In this study, therefore, six E. faecalis isolates from an endodontic environment and two control strains were exposed to subinhibitory concentrations of Penicillin G, Amoxicillin, Doxycycline, Fosfomycin, Tetracycline and Vancomycin and examined for their biofilm formation abilities. The minimum inhibitory concentration (MIC) was determined for all E. faecalis isolates. A culture of the isolate was mixed with a serial dilution series of the respective antibiotic, incubated overnight and the biofilm formation was analyzed using a microtiter plate assay. All isolates were able to form biofilms in the absence of an antibiotic. A significant increase in biofilm formation of up to more than 50% was found in the isolates exposed to subinhibitory concentrations of various antibiotics. Most isolates showed a significant increase in Fosfomycin (7/8), Doxycycline (6/8) and Tetracycline (6/8). Three endodontic isolates showed a significant increase in five of the antibiotics examined at the same time. On exposure to Vancomycin, three endodontic isolates and the two control strains showed an increase. The increase in the ability to form biofilms extended over a concentration range from 1/2 to 1/64 of the MIC concentration. Antibiotics may reach certain niches in the oral cavity at subinhibitory concentrations only. This can increase the biofilm formation by enterococci, and in turn lead to decreased susceptibility of these taxa to antibiotics.